In vitro spermiotoxicity and in vivo adults' biochemical pattern after exposure of the Mediterranean mussel to the sunscreen avobenzone. (1st November 2022) - Bordalo, Diana; Cuccaro, Alessia; De Marchi, Lucia; Soares, Amadeu M.V.M.; Meucci, Valentina; Battaglia, Federica; Pretti, Carlo; Freitas, Rosa
Abstract: Avobenzone (AVO) is one of the most frequent ultraviolet (UV) filters in personal care products (PCPs). The Mediterranean mussel Mytilus galloprovincialis is a bioindicator often used for ecotoxicological research. Since UV filters reach higher peaks during summer in aquatic bodies, coincident with mussels' spawning period, and bivalves are sessile, both male gametes and adults of this species were used in this experiment. Therefore, the present study aimed to assess how AVO affects M. galloprovincialis at different biological levels. In vitro experiments on sperms (30 min-exposure) and in vivo experiments on adults (28 days-exposure) were carried out at 0.1, 1.0 and 10.0 μg/L of AVO concentrations. The oxidative and physiological status together with genotoxicity in exposed sperms were assessed. Several biochemical parameters related to enzymatic antioxidant defences, biotransformation enzymes, cell membrane damage, energy reserves, and neurotoxicity were evaluated in adult mussels. Results of in vitro sperm exposure to AVO showed significant overproduction of superoxide anions and DNA damages in all treatments and decrease in sperm viability at 1.0 and 10.0 μg/L. AVO exposure also led to complete inhibition of motility of sperms at the highest concentration, while a significant increase of curvilinear velocity and decrease of wobble occurred at 1.0 μg/L. In vivo exposed adults exhibited a significant decrease in metabolic capacity at 0.1 μg/L, a significant increase in the total protein content and enzymatic turnover as superoxide dismutase (antioxidant defence) at 10 μg/L. This study revealed an ecological concern related to the high sensitivity of sperms respectively to adults under environmentally relevant concentrations of AVO, underpinning an hypothesis of male reproductive function impairments. Graphical abstract: Image 1 Highlights: Sperm viability decreased at the highest AVO concentrations. AVO caused ROS overproduction and DNA damage in all exposed sperms. Sperm viability and total motility were decreased by AVO environmental levels. Adults increased antioxidant defenses at the highest exposure concentration. Defense mechanisms prevented cellular damage in adults.